(3QSGdI aj GdMQGQI hGdHQhOI hJVGO aYdjgeGs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf eMeO GdWhSi (B: (3SCdfi bGVi GdbVGI HgQGJ hPdc ai SfI SJ hSJjf hSJeGFg s
(3eUhQI Yf GdeJMa GdHQjWGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B512 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B924 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B54 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI (B371) s
Keywords: (3GdcjejGA h GdWHjYjGJs